History of Rhetoric, Volume I : The Art of Persuasion in Greece - Kennedy, George A. (George Alexander), 1928-2022 (Book collections on Project MUSE., 1963)
A concern for the art of persuasion, as rhetoric was anciently defined, was a principal feature of Greek intellectual life. In this study of the complex of subjects labeled "rhetoric," the author explores rhetorical theory and practice from the fifth to the first centuries B.C. Beginning with the creative rhetoric of the pre-Socratic era, the study progresses through the time of Aristotle and the Attic orators and concludes with the ossification of rhetoric into a pedantic discipline during the Hellenistic period. Originally published in 1963. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905